Influencing the UN Framework Convention on Climate Change - Cramer, Laura K.; Njuguna, Lucy; Arango, Jacobo (CGIAR System Organization, 2024)
The United Nations Framework Convention on Climate Change (UNFCCC) is an international environmental treaty aimed at combating climate change. Adopted in 1992 during the Earth Summit in Rio de Janeiro, it sets out a framework for international efforts to address the issue of global warming and its impacts. To do this, the UNFCCC fosters international collaboration on various efforts, including reducing greenhouse gas emissions, enhancing adaptation to experienced and anticipated climate risks, and mobilizing support required for climate action. Under the auspices of the UNFCCC, stakeholders come together at the annual Conference of Parties (COP) and Subsidiary Bodies sessions to deliberate and agree on a way forward on specific issues, particularly on how to operationalize decisions. In this regard, it is crucial to ensure that the priorities and concerns of people in specific contexts are represented in these discussions. The Initiative has therefore focused on documenting how actions to achieve sustainable livestock production can lead to adaptation (building climate resilience and supporting food security and livelihoods) and mitigation (boosting low- emission development). This brief describes the Initiative’s engagement with UNFCCC followed four pathways: (1) influencing the content of the Adaptation Gap Report; (2) participating in the production of the IPCC’sSixth Assessment Report; (3) informing UNFCCC COP negotiations and building the capacity of negotiators in livestock issues; and (4) presenting livestock and climate at successive COPs.